Understanding Trafficking Vulnerabilities amid Covid-19 in India - Sanchita Chatterjee (UIN Sunan Gunung Djati, 2022)
Human trafficking is a complex problem that exists for generations. Both during and after crises like Covid-19, human trafficking thrives to survive while damaging aspects of developmental activities. However, such factors increase the vulnerability of several groups to potential trafficking during a crisis. The situation of medical emergency can put some people in situations where their families' safety is jeopardised. The paper discusses the dynamics of human trafficking with its extended vulnerabilities due to the global pandemic of Covid-19. It also identifies several factors that heighten the insecurity of the vulnerable population in India within countries of origin, transit and destination. It also seeks to understand on how economic instability triggered by the pandemic created a huge loophole within the governmental structure that created fresh conditions of susceptibility in the huge informal labour market in the region.Â